Simple switching signal design for H∞ performance and control of switched time-delay systems. (August 2018) - Lien, Chang-Hua; Yu, Ker-Wei; Hsieh, Jer-Guang; Chung, Long-Yeu; Chen, Jenq-Der
Abstract: In this paper, a simple switching signal design scheme for H ∞ performance analysis and control of switched time-delay systems with linear fractional perturbations is developed. Delay-dependent LMI-based criteria are proposed to achieve the design of switching signal and control. All the LMI problems in our main results can be solved numerically by Matlab LMI toolbox. Wirtinger-based inequality is used in our approach to improve the conservativeness of the past research results. Finally, some numerical examples are illustrated to show the main improvement. Highlights: The results provide less LMI variables and shorter program running time. The design scheme for switching signal is simple and more flexible. The Wirtinger-based inequality is used to improve the results.